A method for enhancing radiation heat transfer on a chromium-molybdenum steel metal surface and a radiation-enhanced chromium-molybdenum steel metal component
Patent Information
- Application Number
- CN202610999296.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-07
- Publication Date
- 2026-10-09
- Estimated Expiration
- 2046-07-07
AI Technical Summary
[0005]有鉴于此,本发明旨在克服现有技术中的缺陷,提出一种铬钼钢金属表面增强辐射传热的方法及辐射增强型铬钼钢金属构件,通过构建梯度多层结构,解决传统涂层结合力差、热膨胀不匹配和辐射效率低的问题
本发明所述的辐射增强型铬钼钢金属构件通过梯度多层结构实现了热膨胀系数的平滑过渡,镍铝过渡层的线膨胀系数介于铬钼钢基材与稀土辐射层之间,可通过自身塑性变形吸收部分热应力,显著缓解因热膨胀差异导致的涂层开裂、剥落现象;制备的金属构件在800℃下抗热震次数≥50,远优于传统单一涂层(通常≤20次),能够适应高温工况下的频繁冷热交替。
Smart Images

Figure CN122503872B_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of heat transfer, and in particular relates to a method for enhancing radiative heat transfer on the surface of chromium-molybdenum steel and a radiation-enhanced chromium-molybdenum steel metal component. Background Technology
[0002] Chromium-molybdenum steel, due to its excellent high-temperature strength, good toughness, and corrosion resistance, is widely used in high-temperature heat transfer applications such as the inner walls of industrial kilns, high-temperature heat exchangers, and boiler heating surfaces. In these applications, heat transfer efficiency directly affects equipment operating energy consumption and production efficiency. Radiative heat transfer, as one of the main heat transfer methods in high-temperature environments, depends heavily on the infrared radiation properties of the chromium-molybdenum steel surface. However, the natural emissivity of pure chromium-molybdenum steel surface in the 1-5μm infrared band (the core radiation band for industrial high-temperature scenarios) is only 0.3-0.5, resulting in low radiative heat transfer efficiency and significant energy waste.
[0003] To address this issue, existing technologies often employ an infrared radiation coating on the surface of chromium-molybdenum steel to enhance its radiation performance. However, existing coating technologies generally suffer from the following key drawbacks: 1. A significant mismatch exists between the coating and the substrate's coefficients of thermal expansion. The coefficient of linear expansion of chromium-molybdenum steel at 500℃ is 14.5 × 10⁻⁶. -6 -15.8×10 -6 / K, while the coefficient of linear expansion of traditional infrared radiation coatings (mostly ceramic-based materials) is typically 8×10. -6 -12×10 -6 1. The difference between / K and the coating is significant. During the heating and cooling cycles under high-temperature conditions, the interface is prone to generating huge thermal stress, leading to failure phenomena such as cracking and peeling of the coating, which seriously affects the service life of the equipment. 2. The bonding strength between the coating and the substrate is insufficient. Most existing coatings are directly applied to the surface of chromium-molybdenum steel using a single spraying process. The coating and the substrate only form a simple mechanical bond, lacking effective metallurgical bonding or continuous phase transition. Under complex conditions such as high-temperature vibration and thermal shock, the coating is prone to peeling off and cannot be used stably for a long time. 3. It is difficult to balance the high-temperature stability and radiation performance of the coating. Although some coatings can achieve high emissivity at room temperature, they are prone to grain growth, increased porosity, and component volatilization when used for a long time in high-temperature environments above 800℃, resulting in a significant decrease in radiation performance. At the same time, the thermal shock resistance of existing coatings is poor. In frequent alternating heating and cooling cycles, the coating structure is easily damaged, further deteriorating the heat transfer stability.
[0004] Therefore, in response to the needs of high-temperature heat transfer scenarios for chromium-molybdenum steel, developing a surface treatment method that can solve problems such as thermal expansion mismatch between coating and substrate, low bonding strength, and poor high-temperature stability, and can significantly improve radiative heat transfer efficiency, has become a pressing technical challenge in this field. Summary of the Invention
[0005] In view of this, the present invention aims to overcome the defects in the prior art and proposes a method for enhancing radiative heat transfer on the surface of chromium-molybdenum steel and a radiation-enhanced chromium-molybdenum steel metal component. By constructing a gradient multilayer structure, the problems of poor adhesion, thermal expansion mismatch and low radiation efficiency of traditional coatings are solved.
[0006] To achieve the above objectives, the technical solution of the present invention is implemented as follows: This invention provides a method for enhancing radiative heat transfer on the surface of chromium-molybdenum steel, comprising the following steps: Step 1 involves pretreating the chromium-molybdenum steel substrate and then cladding a nickel-aluminum alloy onto the surface of the pretreated chromium-molybdenum steel substrate to form a nickel-aluminum transition layer. Step 2 involves coating the nickel-aluminum rare earth material onto the surface of the nickel-aluminum transition layer to form a nickel-aluminum rare earth composite layer. Step 3 involves coating the surface of the nickel-aluminum-rare-earth composite layer with rare-earth radiation material to form a rare-earth infrared radiation layer. Step 4 involves curing the product obtained in step 3.
[0007] Furthermore, the nickel-aluminum alloy in step 1 is Ni 95 Al5 alloy, Ni 80 Al 20 Alloy or Ni 70 Al 30 One of the alloys; the nickel-aluminum alloy in step 1 has a coefficient of linear expansion of 13.0 × 10⁻⁶ at 500°C. -6 -15.0×10 -6 / K.
[0008] Furthermore, the pretreatment step in step 1 specifically involves: degreasing, rust removal, and sandblasting the chromium-molybdenum steel substrate to obtain a surface roughness Ra of 7.5-10μm and a cleanliness level of Sa3; the cladding step in step 1 is arc spraying.
[0009] Through arc spraying, molten nickel-aluminum alloy droplets impact the surface of chromium-molybdenum steel substrate at high speed and spread out, forming a mechanical bond with the rough surface after sandblasting. At the same time, Ni can undergo a slight diffusion reaction with Fe and Cr elements in the steel substrate to form a metallurgical bond, thereby improving the bonding strength between the transition layer and the substrate.
[0010] Furthermore, the nickel-aluminum rare earth material in step 2 comprises the following raw materials in parts by weight: 25-30 parts nickel-aluminum metal powder, 30-40 parts rare earth nano-oxides, and 30-45 parts silica-alumina sol binder; wherein the nickel-aluminum metal powder is Ni 95 Al5 alloy powder, Ni 80 Al 20 Alloy powder or Ni70 Al 30 One of the alloy powders; the particle size D of the nickel-aluminum metal powder 90 The particle size is 1-5 μm; the rare earth nano-oxide is at least one of nano CeO2, nano La2O3, and nano Y2O3; the particle size D of the rare earth nano-oxide is... 90 The wavelength is 100-300 nm; the silicon-aluminum sol binder has a silicon-aluminum molar ratio of Si:Al = 1:1-2 and a solid content of 20-40 wt%; the coating step in step 2 is a cold spray coating.
[0011] The nickel-aluminum metal powder has the same composition as the nickel-aluminum alloy in the transition layer, ensuring the continuity of the interlayer composition, reducing the interfacial energy between the transition layer and the composite layer, and improving the interlayer bonding force. Nano-rare earth oxides, as the second phase component, inhibit grain growth during coating sintering, refine the coating microstructure, and reduce porosity. Simultaneously, as a high-emissivity material in the mid-infrared band, nano-rare earth oxides improve the emissivity of the composite layer, assisting the high-emissivity characteristics of the rare earth infrared radiation functional layer. Aluminum silicate sol bonds the nickel-aluminum metal powder and rare earth nano-oxides at room temperature. During the high-temperature curing stage, the aluminum silicate sol undergoes dehydration and condensation reactions, forming a high-temperature resistant ceramic bonding skeleton, improving the high-temperature stability and corrosion resistance of the composite layer.
[0012] Furthermore, the rare earth radiation material in step 3 comprises the following raw materials in parts by weight: 55-65 parts of rare earth high infrared radiation material, 30-35 parts of silica-alumina sol binder, and 5-10 parts of rare earth nano-oxides; the rare earth nano-oxides are at least one of nano CeO2, nano La2O3, and nano Y2O3, with a particle size D 90 The wavelength is 100-300 nm; the silicon-aluminum sol binder has a silicon-aluminum molar ratio of Si:Al = 1:1-2 and a solid content of 20-40 wt%.
[0013] Furthermore, the rare-earth high-infrared radiation material is a composite oxide with a perovskite structure and the molecular formula is (La). 1 / 3 Ce 1 / 3 RE 1 / 3 )(Mn x Ni 1-x )O 3-δ Where RE is at least one of Y, Sm, or Gd, x = 0.2-0.6, δ = 0.05-0.20, and the particle size D of the composite oxide with perovskite structure is... 90 It is 1-5μm.
[0014] Furthermore, the preparation method of the rare earth high infrared radiation material includes the following steps: a) grinding, drying and calcining the oxide raw material to obtain an intermediate product; b) grinding, drying, pressing, calcining, crushing and air jet milling the intermediate product to obtain the rare earth high infrared radiation material.
[0015] Furthermore, the particle size D of the material after the sand milling step in step a is... 90 The particle size D of the material after the sand milling step in step b is 200-300 nm; the drying step in step a is at a temperature of 120°C for 8-12 hours; the calcination step in step a is at a temperature of 800-1000°C for 4-6 hours; the particle size D of the material after the sand milling step in step b is 200-300 nm. 90 The particle size D of the material after the air jet milling step in step b is 0.5-1.0 μm; the drying step in step b is performed at a temperature of 120°C for 8-12 hours; the pressing step in step b is performed at a pressure of 50-80 MPa; the calcination step in step b is performed at a temperature of 1200-1400°C for 4-8 hours; the particle size D of the material after the air jet milling step in step b is... 90 It is 1-5μm.
[0016] The A-site and B-site of the rare-earth high-infrared radiation material are doped with multiple elements and have oxygen vacancies. Multi-element rare-earth and Mn / Ni doping leads to lattice distortion, while the variable valence characteristics of manganese and nickel introduce oxygen vacancies, reducing the material's band gap and promoting electron transitions between the valence and conduction bands. This enhances the infrared absorption and re-emission capabilities in the 1-5 μm wavelength band, resulting in an emissivity ≥0.92 for the coating. Simultaneously, the material powder D... 90 With a particle size controlled between 1 and 5 μm, it has a high specific surface area and sintering activity, which is conducive to the formation of a dense coating, while avoiding agglomeration and excessive internal stress in the coating caused by excessively small particle size.
[0017] Furthermore, the thickness of the nickel-aluminum transition layer in step 1 is 100-150 μm; the thickness of the nickel-aluminum rare earth composite layer in step 2 is 50-80 μm; and the thickness of the rare earth infrared radiation layer in step 3 is 50-80 μm. The curing step in step 4 is as follows: heating from room temperature to 200℃ at a rate of 3-8℃ / min, holding for 60-90min; heating from 200℃ to 400℃ at a rate of 2-5℃ / min, holding for 90-120min; heating from 400℃ to 800℃ at a rate of 2-5℃ / min, holding for 30-60min; and then cooling with the furnace.
[0018] The gradient multilayer structure, through matching the interlayer thermal expansion coefficients, gradually decreases from the substrate to the rare-earth infrared radiation layer, significantly reducing interfacial thermal stress and minimizing coating cracking and peeling. A metallurgical bond is formed between the chromium-molybdenum steel substrate and the nickel-aluminum transition layer. A continuous phase of nickel-aluminum metal is formed between the nickel-aluminum transition layer and the nickel-aluminum rare-earth composite layer, enhancing interfacial compatibility. The silica-alumina sol is simultaneously ceramized in both the composite layer and the radiation layer, forming a continuous ceramic framework that penetrates both layers, improving the overall high-temperature stability of the coating. Simultaneously, nano-rare-earth oxides penetrate both the composite layer and the radiation layer, filling the pores in the coating and making it more dense.
[0019] The present invention also provides a radiation-enhanced chromium-molybdenum steel metal component, wherein the metal component is made by the method described above; the metal component includes a chromium-molybdenum steel substrate, wherein a nickel-aluminum transition layer, a nickel-aluminum rare earth composite layer and a rare earth infrared radiation layer are sequentially disposed on the surface of the chromium-molybdenum steel substrate from bottom to top; the metal component has an emissivity ≥0.92 in the 1-5μm infrared band.
[0020] The coating has a bonding strength with the chromium-molybdenum steel substrate of ≥30MPa, and the coating has a thermal shock resistance of ≥50 cycles at 800℃.
[0021] Compared with the prior art, the present invention has the following advantages: The radiation-enhanced chromium-molybdenum steel metal component of this invention achieves a smooth transition of thermal expansion coefficient through a gradient multilayer structure. The linear expansion coefficient of the nickel-aluminum transition layer is between that of the chromium-molybdenum steel substrate and the rare earth radiation layer. It can absorb part of the thermal stress through its own plastic deformation, which significantly alleviates the coating cracking and peeling caused by the difference in thermal expansion. The prepared metal component has a thermal shock resistance of ≥50 times at 800℃, which is far superior to the traditional single coating (usually ≤20 times), and can adapt to the frequent alternation of hot and cold under high temperature conditions.
[0022] The nickel-aluminum transition layer of this invention forms a metallurgical bond with the substrate through high-speed impact and slight diffusion reaction of molten droplets formed by arc spraying. At the same time, the composite layer and the transition layer use nickel-aluminum metal powder with the same composition to ensure the continuity of the interlayer composition and reduce the interfacial energy. The silica-alumina sol in the composite layer and the radiation layer are simultaneously ceramicized during the curing process to form a continuous ceramic skeleton that runs through the two layers, further improving the overall adhesion of the coating. Ultimately, the coating and substrate bonding strength is ≥30MPa, ensuring that the coating is stable and does not fall off under complex working conditions such as high temperature vibration and airflow erosion.
[0023] The rare-earth infrared radiation layer of this invention uses a high infrared radiation material doped with multi-element rare earth elements and Ni. Through lattice distortion and the introduction of oxygen vacancies, the absorption and re-emission capabilities in the 1-5μm band are significantly enhanced, and the coating emissivity is ≥0.92, which is significantly improved compared to the surface emissivity of pure chromium-molybdenum steel. At the same time, nano-rare earth oxides penetrate through the composite layer and the radiation layer, filling the pores of the coating, reducing porosity, and further ensuring the stability of radiation performance.
[0024] The composite layer and the aluminosilicate in the radiation layer of the present invention form a high-temperature resistant ceramic bonding skeleton after high-temperature curing. Combined with the inhibitory effect of nano-rare earth oxides on grain growth, the coating has good high-temperature structural stability. When it is in long-term service in a high-temperature environment above 800°C, the radiation performance and structural integrity are not easily degraded. Attached Figure Description
[0025] Figure 1 This is a metallographic micrograph of the gradient coating structure described in Embodiment 1 of the present invention on 15CrMo steel (observed and photographed using a metallographic microscope at 50x magnification). Detailed Implementation
[0026] Unless otherwise defined, the technical terms used in the following embodiments have the same meanings as commonly understood by those skilled in the art. Unless otherwise specified, the experimental reagents used in the following embodiments are conventional biochemical reagents; and the experimental methods described are conventional methods.
[0027] The present invention will be described in detail below with reference to the embodiments.
[0028] Example 1 A method for enhancing radiative heat transfer on the surface of chromium-molybdenum steel metal includes the following steps: (1) Select 15CrMo steel plate with sample size of 100mm×100mm×5mm, and perform degreasing, rust removal and sandblasting treatment in sequence. The surface roughness Ra after treatment is 10μm and the cleanliness is Sa3. (2) A nickel-aluminum transition layer was prepared on the treated 15CrMo steel plate by arc spraying. The material was Ni. 95 Al5 alloy has a coefficient of linear expansion of 13.0 × 10⁻⁶. -6 / K, with a coating thickness of 120μm; (3) Nickel-aluminum rare earth materials are coated onto the surface of the nickel-aluminum transition layer by cold spraying to form a nickel-aluminum rare earth composite layer, wherein the mass ratio of nickel-aluminum rare earth materials is: 25 parts Ni 95 Al5 alloy powder (D) 90 =5μm), 40 parts of nano CeO2 (D 90=200nm), 35 parts of silica-alumina sol binder (Si to Al molar ratio of 1:1, solid content of 35wt%), coating thickness of 80μm; (4) Rare earth radiative material is coated onto the surface of the nickel-aluminum rare earth composite layer by cold spraying to form a rare earth infrared radiative layer. The mass ratio of each component of the rare earth radiative material is: 60 parts rare earth high infrared radiative material (La 1 / 3 Ce 1 / 3 Y 1 / 3 )(Mn 0.2 Ni 0.8 )O 2.80 (D) 90 =5μm), 35 parts of silica-alumina sol binder (Si to Al molar ratio of 1:1, solid content 35wt%), 5 parts of nano CeO2 (D 90 =200nm), with a coating thickness of 80μm; (5) Place the 15CrMo steel plate coated with a gradient multilayer structure into a high-temperature furnace, raise the temperature from room temperature to 200℃ at a rate of 5℃ / min, hold for 90min, raise the temperature from 200℃ to 400℃ at a rate of 5℃ / min, hold for 90min, raise the temperature from 400℃ to 800℃ at a rate of 2℃ / min, hold for 30min, and then cool with the furnace to obtain the final product. Figure 1 As shown, there are no obvious gaps at the interface between the layers, presenting a continuous structure that is "fused together"; the nickel-aluminum transition layer and the 15CrMo steel plate form a local metallurgical bond or element diffusion layer, rather than a simple physical adhesion; the nickel-aluminum rare earth composite layer and the interface between the rare earth infrared radiation layer and the nickel-aluminum transition layer have material compatibility, forming a tight interlocking interface.
[0029] The preparation method of the rare earth high infrared radiation material includes the following steps: a. A mixture of lanthanum oxide, cerium oxide, yttrium oxide, manganese oxide, and nickel oxide is milled (D) 90 The sample was dried at 120°C for 10 hours and then calcined at 800°C for 6 hours to obtain the intermediate product. b. The intermediate product is then milled (D) 90 The rare earth high infrared radiation material (D0.6μm) was obtained by drying at 120℃ for 10 hours, pressing at 60MPa, calcining at 1300℃ for 6 hours, crushing, and air jet milling. 90 (5μm).
[0030] Example 2
[0031] A method for enhancing radiative heat transfer on the surface of chromium-molybdenum steel metal includes the following steps: (1) Select 20CrMo steel plate with sample size of 100mm×100mm×5mm, and perform degreasing, rust removal and sandblasting treatment in sequence. The roughness Ra after sandblasting is 8μm and the cleanliness is Sa3. (2) A nickel-aluminum transition layer was prepared on the treated 20CrMo steel plate by arc spraying. The material was Ni. 80 Al 20 The alloy has a coefficient of linear expansion of 14.0 × 10⁻⁶. -6 / K, with a coating thickness of 150μm; (3) Nickel-aluminum rare earth materials are coated onto the surface of the nickel-aluminum transition layer by cold spraying to form a nickel-aluminum rare earth composite layer; the mass ratio of each component of the nickel-aluminum rare earth material is: 25 parts Ni 80 Al 20 Alloy powder (D) 90 =5μm), 35 parts of nano-La2O3 (D 90 =300nm), 40 parts of silica-alumina sol binder (Si to Al molar ratio of 1:1.5, solid content 30wt%), coating thickness of 60μm; (4) Rare earth radiative material is coated onto the surface of the nickel-aluminum rare earth composite layer by cold spraying to form a rare earth infrared radiative layer. The mass ratio of each component of the rare earth radiative material is: 60 parts rare earth high infrared radiative material (La 1 / 3 Ce 1 / 3 Sm 1 / 3 )(Mn 0.3 Ni 0.7 )O 2.85 (D) 90 =5μm), 35 parts of silica-alumina sol binder (Si to Al molar ratio of 1:1.5, solid content 30wt%), 5 parts of nano-La2O3 (D 90 =300nm), with a coating thickness of 60μm; (5) Place the 20CrMo steel plate coated with gradient multilayer structure into a high-temperature furnace, raise the temperature from room temperature to 200℃ at a rate of 8℃ / min, hold for 60min, raise the temperature from 200℃ to 400℃ at a rate of 5℃ / min, hold for 120min, raise the temperature from 400℃ to 800℃ at a rate of 5℃ / min, hold for 60min, and then cool with the furnace.
[0032] The preparation method of the rare earth high infrared radiation material includes the following steps: a. A mixture of lanthanum oxide, cerium oxide, samarium oxide, manganese oxide, and nickel oxide is milled (D) 90 The sample was dried at 120°C for 8 hours and then calcined at 900°C for 4 hours to obtain the intermediate product. b. The intermediate product is then milled (D) 90The rare earth high infrared radiation material (D0.5μm) was obtained by drying at 120℃ for 8 hours, pressing at 80MPa, calcining at 1200℃ for 8 hours, crushing, and air jet milling. 90 (5μm).
[0033] Example 3
[0034] A method for enhancing radiative heat transfer on the surface of chromium-molybdenum steel metal includes the following steps: (1) Select 30CrMo steel plate with sample size of 100mm×100mm×5mm. Degreasing, rust removal and sandblasting are performed in sequence. The roughness Ra after sandblasting is 10μm and the cleanliness is Sa3.
[0035] (2) A nickel-aluminum transition layer was prepared on the treated 30CrMo steel plate by arc spraying. The material was Ni. 70 Al 30 The alloy has a coefficient of linear expansion of 14.7 × 10⁻⁶. -6 / K, with a coating thickness of 140μm; (3) Nickel-aluminum rare earth materials are coated onto the surface of the nickel-aluminum transition layer by cold spraying to form a nickel-aluminum rare earth composite layer; the mass ratio of each component of the nickel-aluminum rare earth material is: 28 parts Ni 70 Al 30 Alloy powder (D) 90 =2μm), 32 nano-Y2O3 (D 90 =100nm), 40 parts of silica-alumina sol binder (Si to Al molar ratio of 1:2, solid content 25wt%), coating thickness of 70μm; (4) The rare earth radiating material is coated onto the surface of the nickel-aluminum rare earth composite layer by cold spraying to form a rare earth infrared radiating layer; the mass ratio of each component of the rare earth radiating material is: 61 parts rare earth high infrared radiating material (La 1 / 3 Ce 1 / 3 Gd 1 / 3 )(Mn 0.4 Ni 0.6 )O 2.90 (D) 90 =3μm), 32 parts of silica-alumina sol binder (Si to Al molar ratio of 1:2, solid content 25wt%), 7 parts of nano Y2O3 (D 90 =100nm), with a coating thickness of 70μm; (5) Place the 30CrMo steel plate coated with gradient multilayer structure into a high-temperature furnace, raise the temperature from room temperature to 200℃ at a rate of 3℃ / min, hold for 80min, raise the temperature from 200℃ to 400℃ at a rate of 3℃ / min, hold for 100min, raise the temperature from 400℃ to 800℃ at a rate of 2℃ / min, hold for 45min, and then cool with the furnace.
[0036] The preparation method of the rare earth high infrared radiation material includes the following steps: a. A mixture of lanthanum oxide, cerium oxide, gadolinium oxide, manganese oxide, and nickel oxide is milled (D) 90 The sample was dried at 120°C for 12 hours and then calcined at 1000°C for 4 hours to obtain the intermediate product. b. The intermediate product is then milled (D) 90 The rare earth high infrared radiation material (D0.8μm) was obtained by drying at 120℃ for 10 hours, pressing at 50MPa, calcining at 1300℃ for 6 hours, crushing, and air jet milling. 90 (3μm).
[0037] Example 4
[0038] A method for enhancing radiative heat transfer on the surface of chromium-molybdenum steel metal includes the following steps: (1) Select 35CrMo steel plate with sample size of 100mm×100mm×5mm, and perform degreasing, rust removal and sandblasting treatment in sequence. The roughness Ra after sandblasting is 7.5μm and the cleanliness is Sa3 grade. (2) A nickel-aluminum transition layer was prepared on the treated 35CrMo steel plate by arc spraying. The material is Ni 95 Al5 alloy has a coefficient of linear expansion of 13.0 × 10⁻⁶. -6 / K, with a coating thickness of 100μm; (3) Nickel-aluminum rare earth materials are coated onto the surface of the nickel-aluminum transition layer by cold spraying to form a nickel-aluminum rare earth composite layer; the mass ratio of each component of the nickel-aluminum rare earth material is: 30 parts Ni 95 Al5 alloy powder (D) 90 =1μm), 30 parts of a mixed powder of nano CeO2 and nano La2O3 (CeO2 to La2O3 mass ratio of 1:1, D 90 =200nm), 40 parts of silica-alumina sol binder (Si to Al molar ratio of 1:2, solid content of 35wt%), coating thickness of 50μm; (4) Rare earth radiative material is coated onto the surface of the nickel-aluminum rare earth composite layer by cold spraying to form a rare earth infrared radiative layer; the mass ratio of each component of the rare earth radiative material is: 57 parts rare earth high infrared radiative material (La 1 / 3 Ce 1 / 3 Y 1 / 3 )(Mn 0.5 Ni 0.5 )O 2.95 (D) 90=4μm), 35 parts of silica-alumina sol binder (Si to Al molar ratio of 1:2, solid content 35wt%), 8 parts of nano CeO2 and nano La2O3 mixed powder (CeO2 to La2O3 mass ratio of 1:1, D 90 =200nm), with a coating thickness of 80μm; (5) Place the 35CrMo steel plate coated with gradient multilayer structure into a high-temperature furnace, raise the temperature from room temperature to 200℃ at a rate of 5℃ / min, hold for 90min, raise the temperature from 200℃ to 400℃ at a rate of 5℃ / min, hold for 120min, raise the temperature from 400℃ to 800℃ at a rate of 5℃ / min, hold for 60min, and then cool with the furnace.
[0039] The preparation method of the rare earth high infrared radiation material includes the following steps: a. A mixture of lanthanum oxide, cerium oxide, yttrium oxide, manganese oxide, and nickel oxide is milled (D) 90 The sample was dried at 120°C for 11 hours and then calcined at 950°C for 5.5 hours to obtain the intermediate product. b. The intermediate product is then milled (D) 90 The rare earth high infrared radiation material (D1.0μm) was dried at 120℃ for 11 hours, pressed at 70MPa, calcined at 1350℃ for 5.5 hours, crushed, and then air-jet milled to obtain the aforementioned rare earth high infrared radiation material (D1.0μm). 90 (4μm).
[0040] Example 5
[0041] A method for enhancing radiative heat transfer on the surface of chromium-molybdenum steel metal includes the following steps: (1) Select 42CrMo steel plate with sample size of 100mm×100mm×5mm. Degreasing, rust removal and sandblasting were performed in sequence. The roughness Ra after sandblasting was 9μm and the cleanliness was Sa3. (2) A nickel-aluminum transition layer was prepared on the treated 42CrMo steel plate by arc spraying. The material was Ni 95 Al5 alloy has a coefficient of linear expansion of 13.0 × 10⁻⁶. -6 / K, with a coating thickness of 130μm; (3) Nickel-aluminum rare earth materials are coated onto the surface of the nickel-aluminum transition layer by cold spraying to form a nickel-aluminum rare earth composite layer. The mass ratio of each component of the nickel-aluminum rare earth material is: 28 parts Ni 95 Al5 alloy powder (D) 90 =4μm), 36 parts of mixed powder of nano CeO2, nano La2O3 and nano Y2O3 (mass ratio of CeO2, La2O3 and Y2O3 is 1:1:1, D 90=300nm), 36 parts of silica-alumina sol binder (Si to Al molar ratio of 1:1.8, solid content 40wt%), coating thickness of 80μm; (4) Rare earth radiative material is coated onto the surface of the nickel-aluminum rare earth composite layer by cold spraying to form a rare earth infrared radiative layer. The mass ratio of each component of the rare earth radiative material is: 64 parts rare earth high infrared radiative material (La 1 / 3 Ce 1 / 3Sm 1 / 3 )(Mn 0.6 Ni 0.4 )O 2.95 (D) 90 =5μm), 30 parts of silica-alumina sol binder (Si to Al molar ratio of 1:1.8, solid content 40wt%), 6 parts of nano CeO2 (D 90 =200nm), with a coating thickness of 60μm; (5) Place the 42CrMo steel plate coated with gradient multilayer structure into a high-temperature furnace, raise the temperature from room temperature to 200℃ at a rate of 4℃ / min, hold for 70min, raise the temperature from 200℃ to 400℃ at a rate of 4℃ / min, hold for 110min, raise the temperature from 400℃ to 800℃ at a rate of 4℃ / min, hold for 50min, and then cool with the furnace.
[0042] The preparation method of the rare earth high infrared radiation material includes the following steps: a. A mixture of lanthanum oxide, cerium oxide, samarium oxide, manganese oxide, and nickel oxide is milled (D) 90 The sample was dried at 120°C for 9 hours and then calcined at 850°C for 5 hours to obtain the intermediate product. b. The intermediate product is then milled (D) 90 The rare earth high infrared radiation material (D0.9μm) was dried at 120℃ for 12 hours, pressed at 65MPa, calcined at 1400℃ for 4 hours, crushed, and then air-jet milled to obtain the aforementioned rare earth high infrared radiation material (D0.9μm). 90 (5μm).
[0043] Comparative Example 1 The only difference from Example 1 is that the nickel-aluminum transition layer in step (2) and the nickel-aluminum rare earth composite layer in step (3) are absent.
[0044] Comparative Example 2 The only difference from Example 1 is that the nickel-aluminum transition layer in step (2) is not present.
[0045] Comparative Example 3 The only difference from Example 1 is that the nickel-aluminum rare earth composite layer in step (3) is not present.
[0046] Comparative Example 4 The only difference from Example 1 is that the rare earth high infrared radiation material in step (4) is replaced with non-rare earth infrared radiation material iron manganese spinel MnFe2O4 (purity 99%, 800 mesh).
[0047] Performance tests were conducted on the samples from Examples 1-5 and Comparative Examples 1-4: Infrared emissivity in the 1-5 μm band at room temperature was measured using an infrared spectrometer; the coating adhesion strength was tested using the pull-out method; thermal shock resistance was tested by thermal shock cycling at 1000℃, and the number of coating peelings or crackings was recorded; after the thermal shock resistance test, the infrared emissivity in the 1-5 μm band at room temperature was measured using an infrared spectrometer (for thermal shock cycles < 50, the emissivity was measured after the failure cycle termination; for thermal shock cycles ≥ 50, the emissivity was measured after the 50th cycle). The results are shown in Table 1.
[0048] Table 1 Test results of sample performance
[0049] As shown in Table 1, the gradient multilayer structure of the present invention significantly improves the radiative heat transfer performance of the metal surface. Examples 1-5 all exhibit infrared emissivity ≥0.92 in the 1-5 μm band, coating bonding strength ≥30 MPa, and thermal shock resistance ≥50 cycles, with post-thermal shock emissivity exceeding 0.90. Comparative Example 1 (without a transition layer), Comparative Example 2 (without a transition layer but containing a composite layer), and Comparative Example 3 (without a nickel-aluminum rare earth composite layer) show significantly inferior bonding strength and thermal shock resistance compared to the examples, demonstrating the crucial role of the metal transition layer and composite layer in enhancing coating bonding strength and matching thermal stress between the coating and the metal substrate. Comparative Example 4 uses the non-rare earth infrared radiating material iron-manganese spinel MnFe2O4, exhibiting low initial emissivity that decreases significantly after thermal shock, highlighting the irreplaceable role of rare earth materials in providing high emissivity and high-temperature stability of the coating. In summary, the gradient multilayer design of the present invention achieves a balance of high emissivity, high bonding strength, and excellent thermal shock resistance through the synergy of materials and structure, making it suitable for harsh high-temperature operating conditions.
[0050] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention should be included within the protection scope of the present invention.
Claims
1. A method for enhancing radiative heat transfer on the surface of chromium-molybdenum steel, characterized in that: Includes the following steps: Step 1 involves pre-treating the chromium-molybdenum steel substrate and then arc-spraying a nickel-aluminum alloy onto the surface of the pre-treated chromium-molybdenum steel substrate to form a nickel-aluminum transition layer. Step 2 involves coating the nickel-aluminum rare earth material onto the surface of the nickel-aluminum transition layer to form a nickel-aluminum rare earth composite layer. Step 3 involves coating the surface of the nickel-aluminum-rare-earth composite layer with rare-earth radiation material to form a rare-earth infrared radiation layer. Step 4 involves curing the product obtained in step 3. The nickel-aluminum alloy in step 1 has a coefficient of linear expansion of 13.0 × 10⁻⁶ at 500°C. -6 -15.0×10 -6 / K; The nickel-aluminum rare earth material in step 2 comprises the following raw materials in parts by weight: 25-30 parts nickel-aluminum metal powder, 30-40 parts rare earth nano-oxides, and 30-45 parts silica-alumina sol binder; wherein the nickel-aluminum metal powder is Ni 95 Al5 alloy powder, Ni 80 Al 20 Alloy powder or Ni 70 Al 30 One of the alloy powders; the particle size D of the nickel-aluminum metal powder 90 The particle size is 1-5 μm; the rare earth nano-oxide is at least one of nano CeO2, nano La2O3, and nano Y2O3; the particle size D of the rare earth nano-oxide is... 90 The wavelength is 100-300nm; the silicon-aluminum sol binder has a silicon-aluminum molar ratio of Si:Al=1:1-2 and a solid content of 20-40wt%; the coating step in step 2 is cold spraying. The rare earth radiation material in step 3 comprises the following raw materials in parts by weight: 55-65 parts of rare earth high infrared radiation material, 30-35 parts of silica-alumina sol binder, and 5-10 parts of rare earth nano-oxides; the rare earth nano-oxides are at least one of nano CeO2, nano La2O3, and nano Y2O3, with a particle size D 90 The wavelength is 100-300 nm; the silicon-aluminum sol binder has a silicon-aluminum molar ratio of Si:Al = 1:1-2 and a solid content of 20-40 wt%. The aforementioned rare-earth high-infrared radiation material is a composite oxide with a perovskite structure and the molecular formula is (La). 1 / 3 Ce 1 / 3RE 1 / 3 )(Mn x Ni 1-x )O 3-δ Where RE is at least one of Y, Sm, or Gd, x = 0.2-0.6, δ = 0.05-0.20, and the particle size D of the composite oxide with perovskite structure is... 90 1-5μm; The preparation method of the rare earth high infrared radiation material includes the following steps: a) grinding, drying and calcining the oxide raw material to obtain an intermediate product; b) grinding, drying, pressing, calcining, crushing and air jet milling the intermediate product to obtain the rare earth high infrared radiation material. The calcination step in step a is at a temperature of 800-1000℃ and takes 4-6 hours; the calcination step in step b is at a temperature of 1200-1400℃ and takes 4-8 hours. The curing step in step 4 is as follows: heating from room temperature to 200℃ at a rate of 3-8℃ / min, holding for 60-90min; heating from 200℃ to 400℃ at a rate of 2-5℃ / min, holding for 90-120min; heating from 400℃ to 800℃ at a rate of 2-5℃ / min, holding for 30-60min; and then cooling with the furnace.
2. The method for enhancing radiative heat transfer on the surface of chromium-molybdenum steel according to claim 1, characterized in that: The nickel-aluminum alloy in step 1 is Ni 95 Al5 alloy, Ni 80 Al 20 Alloy or Ni 70 Al 30 One type of alloy.
3. The method for enhancing radiative heat transfer on the surface of chromium-molybdenum steel according to claim 1, characterized in that: The pretreatment step in step 1 is as follows: the chromium-molybdenum steel substrate is degreased, derusted and sandblasted, and the surface roughness Ra of the pretreated chromium-molybdenum steel substrate is 7.5-10μm and the cleanliness is Sa3 level.
4. The method for enhancing radiative heat transfer on the surface of chromium-molybdenum steel according to claim 1, characterized in that: The particle size D of the material after the sand milling step in step a is described above. 90 The particle size D of the material after the sand milling step in step b is 200-300 nm; the drying temperature in step a is 120°C and the time is 8-12 hours; 90 The particle size D of the material after the air jet milling step in step b is 0.5-1.0 μm; the drying temperature in step b is 120℃ and the time is 8-12 hours; the pressing pressure in step b is 50-80 MPa; the particle size D of the material after the air jet milling step in step b is... 90 It is 1-5μm.
5. The method for enhancing radiative heat transfer on the surface of chromium-molybdenum steel according to claim 1, characterized in that: The thickness of the nickel-aluminum transition layer in step 1 is 100-150 μm; the thickness of the nickel-aluminum rare earth composite layer in step 2 is 50-80 μm; and the thickness of the rare earth infrared radiation layer in step 3 is 50-80 μm.
6. A radiation-enhanced chromium-molybdenum steel metal component, characterized in that: The metal component is manufactured by the method of any one of claims 1-5; the metal component comprises a chromium-molybdenum steel substrate, and the surface of the chromium-molybdenum steel substrate is provided with a nickel-aluminum transition layer, a nickel-aluminum rare earth composite layer and a rare earth infrared radiation layer from bottom to top; the emissivity of the metal component in the 1-5μm infrared band is ≥0.92.
Citation Information
Patent Citations
High-temperature infrared radiation coating as well as preparation method and application of coating
CN107573731A
Thermophilic corrosion-resistance coating
CN1121538A